(untitled) (International Journal of Engineering and Computer Science, 2017)
The aim of image enhancement is to improve the visual appearance of an image, or to provide a “better transform representation for future automated image processing. Many images like medical images, satellite images, aerial images and even real life photographs suffer from poor contrastand noise. It is necessary to enhance the contrast and remove the noise to increase image quality. Enhancement may be used to restore an image that has suffered some kind of deterioration due to the optics, electronics and/or environment or to enhance certain features of an image.